How to Be a Proponent of Empathy. - Song, Yujia (Ethical Theory & Moral Practice, 2015)
A growing interest across disciplines in the nature of empathy has sparked a debate over the place of empathy in morality. Proponents are eager to capitalize on the apparent close connection between empathy and altruism, while critics point to serious problems in our exercise of empathy - we are naturally biased, empathize too much or too little, and prone to making all sorts of mistakes in empathizing. The proponents have a promising response, that it is not empathy simpliciter, but empathy in some 'proper' form, that does the work they claim for it. This paper aims to propose a cautiously optimistic position for the proponent by rethinking the suggested approach. I argue that empathy plays two important roles in morality, one epistemic and the other relational, but the proponent must be careful not to exaggerate the contribution that empathy, even in its 'proper' form, can make to our moral life.